Sorghum grain mold: the scope of institutional innovations to support sorghum based rural livelihoods - Hall, A.; Bandyopadhyay, Ranajit; Chandrashekar, A.; Shewry, P.; Bandyopadhyay, A.J.; Chandrashekar, R. (2000)
The introduction of photoperiod-insensitive, short-and medium-duration, high-yielding rainy season (kharif) sorghum (Sorghum bicolor (L.) Moench) hybrids in India more than 20 years ago has led to dramatic increases in grain yield (from 587 kg ha -1 in 1970 to 1407 kg ha -1 in 1996). This was accompanied by high levels of adoption (80% of rainy season crops) by farmers in the major sorghum-growing state of Maharashtra. Despite this achievement, hybrid rainy season sorghum grains suffer from infection and colonization by several fungi towards the end of the growing season, often associated with late rains. This infection results in grain mold often referred to as "blackening". There is little doubt that in its broadest sense grain mold constitutes one of the most important biotic constraints to sorghum improvement and production worldwide (Frederiksen et al. 1982; Louvel and Arnoud 1984; ICRISAT 1987). Certain grain mold pathogens have repeatedly been associated with losses in seed mass (Castor and Frederiksen 1980; Hepperly et al. 1982), grain density (Castor 1981; Ibrahim et al. 1985), and percent germination (Castor 1981). Other types of damage that arise from grain mold relate to storage quality (Hodges et al. 1999), food and feed processing quality, and market value. Several mold fungi are producers of potent mycotoxins that are harmful to human and animal health and productivity. The International Crops Research Institute for the Semi-Arid Tropics (ICRISAT), Patancheru, India has estimated US$ 130 million as total losses due to grain mold in the semi-arid tropical areas of Asia and Africa (ICRISAT 1992). The poverty implications of grain mold are associated with loss of access to food, exposure to health risks through contaminated food, and income losses through lower prices. While the cause, scope, and implications of the problem are clear, what possible avenues are open to address this problem? On the whole results have not been promising. Several approaches to control grain mold have been attempted. These include fungicidal control and integrating adjustments to sowing dates with high-yielding and relatively less susceptible hybrids (Forbes et. 2000. Technical and institutional options for sorghum grain mold management and the potential for impact on the poor: overview and recommendations. Pages 7-33 in Technical and institutional options for sorghum grain mold management: proceedings of an international consultation, 18-19 May 2000, ICRISAT, Patancheru, India (Chandrashekar, A., Bandyopadhyay, R., and Hall, A.J., eds.). Patancheru 502 324, Andhra Pradesh, India: International Crops Research Institute for the Semi-Arid Tropics.